Financial Analysis of lipCat Private Ltd-A Switzerland based Cosmetics Start-up Company - Deshmukh, Swapnil (2010)
The aim of this report is to perform a financial and non financial analysis with the help of published literature for lipCat Private Limited – a Switzerland based decorative cosmetics small size family business firm which plans to set itself up in the turbulent and competitive Swiss cosmetics industry. Strategic tools and techniques such as SWOT, PESTLE and FIVE FORCES analysis have been employed to perform the non financial analysis. The financial analysis of the company has been incorporated as per the information provided by the owner of the company. The three core financial statements, viz. balance sheet, the income statement and cash flow statements represent the financial analysis. Discounted cash flow techniques such as Net Present Value and Internal Rate of Return have been used in order to judge the financial viability of the project. It also highlights the obstacles faced while preparing the analysis by employing different financial techniques generally used to analyse multinational projects or projects with much larger capital base. The conclusion presented is based on the below analysis. The Financial Strategy for the company has been included in the group part of this project.